2015
DOI: 10.1186/s13046-015-0193-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TMEM158 contributes to ovarian carcinogenesis

Abstract: BackgroundTransmembrane protein 158 (TMEM158) is a recently identified upregulated gene during Ras-induced senescence. Its association with various cancers has been recently reported. However, the expression and biological function of TMEM158 in ovarian cancer is still unclear. This study was aimed to elucidate the roles of TMEM158 in cell proliferation, adhesion and cell invasion of ovarian cancer cells.MethodsWe analyzed TMEM158 mRNA level in ovarian cancer tissues and adjacent no-tumorous tissues by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…By interaction with Smad complex (Smad‐mediated canonical or noncanonical signaling pathway), several transcription factors are initiated so as to result in EMT (Giannelli et al, ; Moustakas & Heldin, ; Yu et al, ). Cheng et al () reported that TMEM158 promoted the migration and adhesion of ovarian cancer cells by upregulation of TGFβ1, BMP4, ICAM1, and IVCAM1. According to the TCGA data set, interestingly, a significant positive association within the expression profile of TMEM158 and TGFβ1 was really existed in PC samples.…”
Section: Discussionmentioning
confidence: 99%
“…By interaction with Smad complex (Smad‐mediated canonical or noncanonical signaling pathway), several transcription factors are initiated so as to result in EMT (Giannelli et al, ; Moustakas & Heldin, ; Yu et al, ). Cheng et al () reported that TMEM158 promoted the migration and adhesion of ovarian cancer cells by upregulation of TGFβ1, BMP4, ICAM1, and IVCAM1. According to the TCGA data set, interestingly, a significant positive association within the expression profile of TMEM158 and TGFβ1 was really existed in PC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is the leading cause of cancer-associated mortality in gynecology worldwide. MEOC is successfully treated in <40% of women, due to the lack of effective screening strategies and the non-specific nature of early signs and symptoms associated with this disease, resulting in an advanced stage diagnosis for the majority of patients (15,16). Tumor recurrence and metastasis are considered the major reasons for poor clinical outcomes and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 However, little is known regarding the association between TMEMs and osteosarcoma. TMEM119, a member of the transmembrane protein family and also known as osteoblast induction factor (Obif), is O -glycosylated at its N-terminal region.…”
Section: Introductionmentioning
confidence: 99%